PENINGKATKAN HASIL BELAJAR PKN KELAS V MELALUI MODEL ACTIVE LEARNING (TIPE ROLE REVERSAL QUESTION) SDN 4 DOPLANG KECAMATAN JATI KABUPATEN BLORA - Ambar Susilo Murti (Universitas PGRI Madiun, 2016)
Constitution No. 20 of 2003, concerning Citizenship Education (PKN) is a compulsory subject for primary education, secondary, and compulsory subjects for higher education. The purpose of this study is to improve learning outcomes Civics using Active Learning Model Type Question Role Reversal in Class V SDN 4 Doplang Jati district of Blora. This research was a class action (classroom action research). The stages as follows: (1) planning, (2) implementation, (3) observation and (4) reflection. The result of research indicating that students who received grades ≥70 the first cycle increased by 25% from the initial 44% to 69%. Then students who scored ≥70 on the second cycle increased 28% to 97%. The average value of the first cycle increased by 8.75% from 66.53 into 75.28 early in the first cycle and then the second cycle of the average value increased again by 10.97% to 86.25. Researchers suggest teachers should encourage students to be more daring in expressing opinions, questions and ideas that are not held only in Civics alone but on other subjects. In addition, teachers are expected to use active learning model of the type of role reversal question in improving student learning outcomes in other subjects. As for the school is expected to provide training to teachers on implementing learning activities are innovative and creative. Keywords: active learning, civic education, learning outcomes.